Awareness of Self-Examination of Lump in the Breast Among Married Women of Karachi (Medical Forum Monthly, 2023)
Objective: To assess the knowledge and enactment of breast self-examination and to appraise the repercussion with educational status of the participant.Study Design: A cross sectional studyPlace and Duration of Study: This study was conducted at Jinnah Postgraduate Medical Centre Karachi, Dr. Ruth K. M. Pfau Civil Hospital Karachi, Fauji Foundation Hospital (Somh) Karachi, Dar ul Sehat Hospital Karachi from March 2022 to October 2022.Materials and Methods: A cross sectional study was conducted on a sample size of 400 married females. The sample was taken through non probability purposive sampling. An informed verbal consent was taken from the females. A pilot study was conducted to assess the validity of questionnaire. A structured questionnaire was distributed which was filled. Data was analyzed using SPSS Version 22 with 95% confidence interval, margin of error was taken as 5% and P-value 0.05 was considered significant.Results: A study was conducted to assess the awareness of self-examination of lump in the breast among married women of Karachi. Overall out of 400 women, 55.3% (p=0.000) had heard about breast self-examination but 84.0% (p=0.000) had no knowledge regarding the steps of self-examination. Similarly, 22.3%(p=0.001), 47.0%(p=0.003), 36.5%(p=0.045) and 76.5%(p= 0.000) women had no knowledge that small lump in the breast, discharge from the nipple, unusual changes in the shape of the breast can lead to breast cancer and breastfeeding can reduce the risk for having breast cancer respectively. 88.3% (p=0.005) women believed that awareness campaigns regarding breast cancer should be initiated under government supervision and 30.3 %( p=0.000) believed that women should teach their daughters regarding self-examination of breast at the age of menarche.Conclusion: This study suggests that women of Karachi have moderate level of knowledge regarding breast self-examination. We believe that awareness programs should be engaging, encouraging with precedent pedagogic about common pathological conditions, clinical features, risk factors and relieving factors, screening methods to ensure early detection and reduction of mortality caused by breast cancer in females.